Protecting the Still Functioning Ecosystem: The Case of the Prairie Pothole Wetlands - John H. Davidson (Washington University Journal of Law & Policy, 2002)
This Essay discusses the challenges presented by attempts to ensure consistency between agricultural production and ecosystem/biodiversity protection. Additionally, this Essay examines mechanisms for achieving ecosystem protection. Although the notion of a sustainable agriculture provides a backdrop for analysis, this phrase seems far too general to support a meaningful discussion of how we manage real-world agriculture “on the ground.” Therefore, this Essay emphasizes one geographic region and one major natural resource within that region: the “Prairie Pothole” systems of streams, headwaters, wetlands, glacial aquifers, and rivers of the north central United States. This Essay addresses the practical and basic issue of whether twenty-first century agriculture can be organized and managed so that it exists in harmony with surrounding ecosystems.
Keywords: Ecosystem management; Sustainable development; Agriculture; Wetlands; Watersheds; Agricultural policy; Biodiversity; Environmental policy; Sustainable agriculture; Wetland conservation; United States